Synthesis of a device for anti-jamming reception of signals of tonal rail circuits on the background of additive five-component interference - Panchenko, Sergii; Ananieva, Olha; Babaiev, Mykhailo; Davidenko, Mykhailo; Panchenko, Vladyslav (Eastern-European Journal of Enterprise Technologies, 2021)
An optimal receiving device for information signals of tonal rail circuits has been synthesized. The signals are observed against the background of an additive five-component interference. The first component of the interference is broadband Gaussian noise. The other four components of the interference are structurally determined: single impulse interference, interference from an adjacent tonal rail circuit, and multiharmonic interference from alternating traction current combined with the power line and from the locomotive traction converter. The presence of a complex of interference leads to errors in decision-making regarding the regulation of train traffic. This puts the participants in this movement before the danger of threatening emergencies. Therefore, it is necessary to develop and study means of noise-immune reception of information signals and the formation of dispatch decisions. The decision on the presence or absence of a signal is made by comparing two values of the mean square of the approximation error. This error is understood as the difference between the input voltage of the receiver and the sum of the signal with structurally determined interference. The first value of the error is calculated assuming the presence of a signal in a mixture with structurally determined noise. The second error value is calculated on the assumption that there is no signal in this mixture. The noise component is assumed to be present in both cases. The solution corresponds to a channel with a lower mean squared error. The block diagram of the device is presented. Analytically, it has been shown that the average value of the error in recognizing situations of presence or absence of a signal is two orders of magnitude less than the admissible value according to regulatory requirements. High noise immunity of the developed device will improve the safety of train traffic